1997
DOI: 10.1164/ajrccm.156.5.9610064
|View full text |Cite
|
Sign up to set email alerts
|

Release of RANTES, MIP-1 α , and MCP-1 into Asthmatic Airways Following Endobronchial Allergen Challenge

Abstract: We have investigated the presence of regulated on activation, normal T-cell expressed and probably secreted (RANTES), macrophage inflammatory peptide-1 alpha (MIP-1 alpha), and macrophage chemotactic peptide (MCP-1) in the bronchoalveolar lavage fluid (BALF) obtained from normal (n = 7) and stable asthmatic subjects (n = 8), and studied their kinetic release into asthmatic airways following endobronchial allergen challenge (n = 18). Measurements of RANTES, MIP-1 alpha, and MCP-1 in 10 times (10x) concentrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
136
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(146 citation statements)
references
References 33 publications
7
136
0
3
Order By: Relevance
“…Fc⑀RI-and CCR1-activated RBL-CCR1 Cells-CCL2 plays a critical role in activation and accumulation of leukocytes in allergic inflammatory tissues (3,(7)(8)(9)15). To examine whether cross-talk between Fc⑀RI-and CCR-mediated signaling pathways in mast cells is involved in expression of this chemokine, we used RBL-2H3 cells expressing human CCR1, a model cell line of mucosal type mast cells.…”
Section: Ccl2 Production and Mapk Activation Are Enhanced Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Fc⑀RI-and CCR1-activated RBL-CCR1 Cells-CCL2 plays a critical role in activation and accumulation of leukocytes in allergic inflammatory tissues (3,(7)(8)(9)15). To examine whether cross-talk between Fc⑀RI-and CCR-mediated signaling pathways in mast cells is involved in expression of this chemokine, we used RBL-2H3 cells expressing human CCR1, a model cell line of mucosal type mast cells.…”
Section: Ccl2 Production and Mapk Activation Are Enhanced Inmentioning
confidence: 99%
“…Some chemokines, such as CCL2/MCP-1 (monocyte chemotactic protein 1), CCL3/MIP-1␣ (macrophage inflammatory protein-1␣), CCL5/RANTES (regulated upon activation, normal T-cell expressed and secreted), and CCL11/eotaxin-1, have been reported to activate mouse, rat, or human mast cells (3)(4)(5)(6). Abundant expression of these CC chemokines and accumulation of leukocytes has also been observed in allergic inflammatory tissues (7)(8)(9). It is very likely that Fc⑀RI and CCR We previously found that CCL3 acts as a co-stimulator for Fc⑀RI-mediated degranulation in conjunctival mast cells using CCL3-deficient mice (10).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…41 CCL2 mediates airway hyperactivity in normal and allergic mice and directly induces in vitro pulmonary mast cell degranulation. 42 Several human studies demonstrate the upregulation of CCL2 during asthmatic responses, 43,44 and CCL2 protein expression in bronchial tissue is significantly higher in subjects with asthma than in control subjects. 43 In our study, plasma CCL2 protein levels were higher in the case than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which eosinophils are recruited are complex but appear to involve the elaboration of cytokines such as IL-3, IL-5, and granulocyte-macrophage colonystimulating factor (GM-CSF), as well as the CC-chemokines "regulated on activation, normal T-cells expressed and secreted" (RANTES), monocyte chemoattractant protein (MCP)-3, and MCP-4 [30,31]. In particular, IL-5 selectively promotes eosinophil function [32] and together with IL-3 and GM-CSF, activates eosinophils to release more sulphidopeptide leukotrienes and secrete cationic proteins toxic to the airway epithelium [30].…”
Section: Discussionmentioning
confidence: 99%